Evolution and Mechanism of Cesium Lead Bromide Nanostructures in Oleylamine‐Rich System by Hot‐Injection Method. Issue 1 (20th October 2022) - Li, Huazheng; Lu, Wangwei; Zhao, Gaoling; Song, Bin; Dong, Weixia; Han, Gaorong
Abstract: Due to the ultrafast nucleation and growth rates of perovskite nanostructures during the synthesis, the products are difficult to control, such as its derivatives (e.g., Cs4 PbBr6 ) often appear. Here, the hot‐injection method is ameliorated by using oleylamine (OAm) instead of octadecene as solvent. The results reveal that in OAm‐rich system, the pure nanostructures with different Pb/Br ratios (CsBr, Cs4 PbBr6, and CsPbBr3 ) can be obtained at different reaction temperatures, and thus controlling the Pb‐Br linkage and the interconnection of [PbBr6 ] 4− octahedra, and resulting in the formation of different nanostructures. As the reaction temperature increases from 120 to 180 °C, the products change from lead‐free CsBr nanocrystals to poor‐lead Cs4 PbBr6 nanocrystals and finally to normal CsPbBr3 nanocubes and nanowires. Moreover, the synthesized CsPbBr3 nanowires exhibit an emission peak at 521 nm, full width at half maximum (FWHM) of 19 nm, with photoluminescence quantum yields (PLQY) of 64.9%, and high stability. Furthermore, the white light‐emitting diode (WLED) devices are successfully fabricated based on the obtained CsPbBr3 nanowires, showing high‐intensity white light and high stability without any encapsulation. Remarkably, this work provides a new approach for elucidating the synthesis mechanism of perovskite nanomaterials and their applications. Abstract : This study employed oleylamine (OAm) as solvent to replace traditional octadecene (ODE) in hot‐injection method, OAm and oleic acid (OA) still as ligands, which can control the Pb‐Br linkage and the interconnection of [PbBr6 ] 4− octahedra, and resulting in the formation of different nanostructures (CsBr, Cs4 PbBr6, and CsPbBr3 ). In addition, the evolution process and mechanism are also systematically studied.